(untitled) - Parrack, Jim; 1992-; Fukuhara, Karen; 1975-; 1972-; Harbour, David; (Musician); Common; Meraz, Alex; Beach, Adam; 1985-; 1959-; et al. ([Burbank, California], 2016)
U.S. intelligence officer Amanda Waller has determined that only a secret group of despicable individuals with nothing to lose can avert a potential apocalypse. So, she has assembled the worlds most dangerous super villains, given them a powerful arsenal of weapons, and sent them off on a suicide mission.
Keywords: Criminals; Drama; Supervillains; Drama; Joker (Fictitious character); Drama; Drama; Drama; Supervillains; Drama; United States; Intelligence officers; Criminals; Drama; Feature films; Fiction films; Video recordings for people with visual disabilities; Video recordings for the hearing impaired; Action and adventure films; Fantasy films; Fiction films; Action and adventure films; Fantasy films; Films for the hearing impaired; Films for people with visual disabilities; Feature films